Literature Review: Development of Credit Union Research Topics Perspectives in The Field of Financial Accounting - Setyaningrum, Putri; Carolina, Anita (Yayasan Ilomata, 2024)
In the modern era, technological developments are changing so rapidly that they are causing social imbalances, including in the business world. Current entities must be able to adapt to changes in the modern era, one of which is the non-profit Credit Union entity. The purpose of this research is to examine trends in mapping the development of Credit Union research because considering the current conditions, many non-profit entities need information to make decisions quickly, accurately and accountably. This research uses descriptive quantitative methods with a Literature Review model using VOSviewer and Publish or Perish. The data used is secondary data obtained from the official website of the Scopus journal. The research conducted focuses on the sub areas of Financial Inclusion, Consumer Welfare, Commercial Banks and Cooperatives. The research results found a total of 200 Scopus articles from 2018 to 2024 and sorting was carried out to find articles that were relevant to Credit Unions. The results of this sorting found 59 Credit Union articles. Thus, the sample size of this research was 59 articles from the 200 articles found. The development of Credit Unions with analysis of topics, keywords, authors, journal names, organizations and countries is the result of research mapping. Researchers also found that the development of Credit Union research fluctuated every year based on the results of the researchers' analysis. The contribution of this research is to provide an overview of a broader research area for future researchers in the Credit Union research topic focused on financial accounting.